Mecanismos De Sinalização Celular Envolvidos Na Secreção De Il-8 Por Células Epiteliais Durante A Interação Com Histoplasma Capsulatum, Quimiotipos I E Ii - Alcantara, Cristiane [UNIFESP] (2018)
Histoplasma capsulatum var. capsulatum is the causative agent of histoplasmosis, a systemic human mycosis with a worldwide distribution. The absence or presence of ( 1,3)glucan on the yeast surface of H. capsulatum classifies the isolates of this fungus into chemotypes I or II, respectively. In this work, we verified that, by indirect immunofluorescence and flow cytometry, isolates 496 and 268 of H. capsulatum showed reactivity with the monoclonal antibody that recognizes ( 1,3)glucan, thus classifying isolates 496 and 268 as being of chemotype II. Subsequently, from the cultures of these isolates, we spontaneously selected mutants of H. capsulatum that did not have ( 1,3)glucan on their surface. These mutants were named 496L and 268L and, in contrast to wild isolates, did not possess ( 1,3)glucan on the fungal surface and, when cultured in a solid medium, formed smooth colonies. We demonstrated that both chemotype II isolates (496 and 268) and their respective mutants induced, at similar levels, IL8 chemokine secretion by A549 human lung epithelial cells. We observed that the wildtype G217B chemotype isolate also induced a statistically significant increase in IL8 levels relative to the basal levels secreted by epithelial cells, but this secretion was lower when compared to the secretion promoted by the chemotype II fungus 268. We then analyzed some cell signaling pathways that are activated by these fungi in A549 cells. Our results demonstrated that the contact of the A549 cells with yeasts of H. capsulatum, isolated 268 and G217B and with the mutant 268L, promoted the activation of SFKs, Syk and PKC δ. In addition, using specific inhibitors for the activation of SFKs (PP2) and Syk (PRT062607), we found that the activation of SFKs was more relevant for IL8 secretion when the cells were infected with the H. capsulatum 268 isolate and its 268L mutant, whereas Syk activation was important for IL8 secretion during infection with G217B. On the other hand, using a PKC δ inhibitor (PIPKC δ), we observed that activation of PKC δ is important for IL8 secretion by A549 epithelial cells during infection with both 268 and G217B isolates and or the mutant (268L). In addition, during the interaction of A549 cells with the fungi studied, there is a feedback between SFKs and Syk. Thus, together, these results show for the first time that H. capsulatum chemotypes I and II promote, in human epithelial cells, different levels of IL8 that are dependent on the different signaling pathways.